Refurnishing the Grunig Edifice: Strategic Public Relations Management, Strategic Communication and Organizational Leadership - De Bussy, Nigel (Routledge, 2013)
This chapter discusses the formidable challenge identified by James E. Grunig in 2006 of institutionalizing strategic public relations as a bridging rather than a buffering activity, so that strategic public relations management becomes standard in most organizations and most people think of public relations that way. The concept of strategic public relations management is contrasted with strategic communication, stakeholder management and corporate social responsibility. The chapter concludes that strategic public relations management (when properly understood) is the responsibility of organizational leaders at all levels and from a variety of disciplines - not just public relations specialists alone.